PENGEMBANGAN E-BOOK BERBASIS AUGMENTED REALITY: INOVASI MEDIA PEMBELAJARAN INTERAKTIF PADA JARINGAN KOMPUTER DAN INTERNET - Usman, Khadaffy; Febriati, Farida; Arnidah (STKIP Citra Bakti, 2025)
This research aims to develop learning media in the form of e-books based on Augmented Reality (AR) as an interactive innovation in delivering computer network and internet material in Informatics subjects. The research method used is Research and Development (R&D) with the ADDIE development model, as well as a mixed methods approach to obtain qualitative and quantitative data. The research was conducted at SMA Negeri 14 Maros involving 112 students who were selected purposively. Validation was conducted by material and media experts, showing that the e-book developed had met the eligibility criteria. The limited trial involved three students and showed a practicality level of 89%, while the assessment from the teacher obtained a score of 90%, both of which were included in the very practical category. The large-scale trial was conducted on 35 students with a pretest result of 39% and a posttest of 90%, which showed a significant increase in learning outcomes and the effectiveness of the media was in the very effective category. This e-book successfully integrates interactive visual elements through AR technology so as to increase students' motivation, concept understanding, and overall learning experience. Thus, this AR-based e-book is declared valid, practical, and effective and feasible to be implemented in learning Informatics at the high school level.